Extending employment entitlements to non-standard workers: Alternative models for long service leave portability. (February 2016) - Markey, Ray; Ferris, Shauna; McIvor, Joseph; Thornthwaite, Louise; Wright, Chris F; Muhidin, Salut; O'Neill, Sharron; Parr, Nick
This article contributes to the emerging scholarship on institutional and regulatory innovations to extend core employment protections to workers on non-standard contracts by examining different policy models that could potentially improve access to statutory long service leave entitlements in Australia. With the growth of casual, contract and short-term employment reducing access to this entitlement for many workers, there have been calls for the creation of a national long service leave scheme that would be portable between employers, so that the benefit is more generally available to workers over the course of their working life. The article proposes three possible models for implementing a portable long service leave scheme. These are evaluated with regard to the relative costs and benefits for employers and workers and implementation issues for governments. We find that the three models distribute risks, costs and benefits differently between the stakeholders, and any model adopted will involve trade-offs.